Practice‐setting and surgeon characteristics heavily influence the decision to perform partial nephrectomy among American Urologic Association surgeons. (13th April 2012) - Weight, Christopher J.; Crispen, Paul L.; Breau, Rodney H.; Kim, Simon P.; Lohse, Christine M.; Boorjian, Stephen A.; Thompson, R. Houston; Leibovich, Bradley C.
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? There is great variability in the utilization of partial nephrectomy, but the causes of these variations are not well understood. The present study underscores the already observed phenomenon of surgical volume influencing surgical planning and outcomes, but it gets at why this might be so. We observe that high‐volume renal surgeons have different thresholds of 'technical feasibility'. Objective To investigate why there continues to be wide variability in the application of partial nephrectomy (PN) for treating small renal masses despite guidelines in the US and Europe stating that a PN is a standard of care for a patient with a T1 renal mass. Patients and Methods In June 2009, 764 surgeon‐members of the American Urologic Association (AUA) participated in a survey evaluating the management of renal masses. Renal mass complexity was graded by nephrometry score (NS). Multivariable logistic regression models with generalized estimating equations were constructed to evaluate how tumour, surgeon and practice‐setting characteristics influence the use of PN. Results The survey response rate was 19%. Each urological surgeon responded to eight scenarios, providing 6112 evaluable cases. Tumour NS ranged from 4 to 10, and each unit increase in NS was associated with 59% increased likelihood of a surgeon offering RN on multivariable analysis (odds ratio [OR] = 1.59; 95% CI: 1.52–1.64). When holding patient and tumour characteristics constant, the following surgeon and practice‐setting characteristics significantly increased the odds of offering a PN: increasing renal case volume (OR = 1.57; 95% CI: 1.27–1.95), academic practice (OR = 1.80; 95% CI: 1.42–2.29), increasing PN % volume (OR = 3.7; 95% CI: 2.46–5.55) and younger surgeon age (≤40 vs >50 years) (OR = 1.64; 95% CI: 1.35–1.96). Conclusion The characteristics of a surgeon and the setting in which he or she practices influence the utilization of PN, the adherence to professional guidelines, and the threshold of tumour complexity at which a surgeon stops offering PN.